Detecting Relative Amplitude of IR Signals with Active Sensors and Its Application to a Positioning System - Elena Aparicio-Esteve; Álvaro Hernández; Jesús Ureña; José Manuel Villadangos; Sergio Lluva; María Carmen Pérez-Rubio (Applied Sciences, 2020)
Nowadays, there is an increasing interest in smart systems, e.g., smart metering or smart spaces, for which active sensing plays an important role. In such systems, the sample or environment to be measured is irradiated with a signal (acoustic, infrared, radio-frequency…) and some of their features are determined from the transmitted or reflected part of the original signal. In this work, infrared (IR) signals are emitted from different sources (four in this case) and received by a unique quadrature angular diversity aperture (QADA) sensor. A code division multiple access (CDMA) technique is used to deal with the simultaneous transmission of all the signals and their separation (depending on the source) at the receiver’s processing stage. Furthermore, the use of correlation techniques allows the receiver to determine the amount of energy received from each transmitter, by quantifying the main correlation peaks. This technique can be used in any system requiring active sensing; in the particular case of the IR positioning system presented here, the relative amplitudes of those peaks are used to determine the central incidence point of the light from each emitter on the QADA. The proposal tackles the typical phenomena, such as distortions caused by the transducer impulse response, the near-far effect in CDMA-based systems, multipath transmissions, the correlation degradation from non-coherent demodulations, etc. Finally, for each emitter, the angle of incidence on the QADA receiver is estimated, assuming that it is on a horizontal plane, although with any rotation on the vertical axis Z. With the estimated angles and the known positions of the LED emitters, the position (x, y, z) of the receiver is determined. The system is validated at different positions in a volume of 3 × 3 × 3.4 m3 obtaining average errors of 7.1, 5.4, and 47.3 cm in the X, Y and Z axes, respectively.